(untitled) (Health Renaissance, 2017)
Background: Destructive surgery is the management option offered to patients when further retention of the globe is unlikely and can affect ocular and general morbidity. Objective: To determine the frequency and indications for destructive eye surgeries in patients attending a tertiary hospital, Eastern Nepal. Methods: A retrospective analysis of clinical records of all the tructive eye surgeries from April 2008 to March 2013 at a tertiary hospital, Eastern Nepal was carried out. Patients’ history, demographic characteristics and indications for the procedure were studied. Results: A total of 88 eyes of 88 patients, who had undergone destructive eye surgery, were reviewed. The mean age of the patient was 22.89 ± 23.49 years, median 9.5 years, with a range of 1.5 months to 80 years. Male: Female ratio was 1:1.04. Enucleation was the most common surgery performed in 46 eyes (52.3%), followed by evisceration in 30 eyes (34.1%) and exenteration in 12 eyes (13.6%). The destructive eye surgery in our study accounted for 51% neoplasms, 17% ocular trauma, 15.9% ocular infection, 10.2% anterior staphyloma and 5.7% painful blind eye. The most common indication for destructive eye surgery was enucleation (60.8%) for retinoblastoma followed by evisceration (46.6%) for open globe injury and exentration (33.3%) for sebaceous gland carcinoma. Conclusions: Enucleation was the most common destructive eye surgery performed. Retinoblastoma, ocular trauma and sebaceous gland carcinoma were the most common indications for destructive eye surgery. Health Renaissance 2015;13 (3): 161-168